Proposed modification of the eighth edition of the AJCC-ypTNM staging system of esophageal squamous cell cancer treated with neoadjuvant chemotherapy: Unification of the AJCC staging system and the Japanese classification. Issue 8 (August 2022) - Oshikiri, Taro; Goto, Hironobu; Kato, Takashi; Sawada, Ryuichiro; Harada, Hitoshi; Urakawa, Naoki; Hasegawa, Hiroshi; Kanaji, Shingo; Yamashita, Kimihiro; Matsuda, Takeru; Fujino, Yasuhiro; Tominaga, Masahiro; et al.
Abstract: Background: The eighth edition of the American Joint Committee on Cancer (AJCC) tumor node metastasis (AJCC-TNM 8th) system adopted the newly separate post-neoadjuvant pathologic stage group (ypTNM). However, it is not compatible with the Japanese pathologic classification after neoadjuvant chemotherapy (JPN-CT-pTNM). The aim of this study is to clarify the subjects of the AJCC-ypTNM 8th and propose a unification of the AJCC and Japanese systems to create novel AJCC-CT-pTNM 8th. Methods: Participants were 304 esophageal squamous cell carcinoma (ESCC) patients who underwent neoadjuvant chemotherapy followed by 3 stage esophagectomy between 2010 and 2019. Predictive probabilities of pN, pM in AJCC-ypTNM 8th and JPN-CT-pTNM 11th systems were evaluated to propose novel system. Results: In training data from 234 patients, the overall survival rate was statistically better for ypStage IIIA than ypStage II (P = 0.040) resulting in staging inversion in AJCC-ypTNM 8th. Predictive probability of pathological N status in AJCC-ypTNM 8th (Akaike Information Criterion: AIC = 979.53) was superior to that in JPN-CT-pTNM 11th (AIC = 999.07). In AJCC-ypTNM 8th, 71% (15/21) of ypM1 diseases were supraclavicular lymph nodes (No. 104 L/N as regional in JPN-CT-pTNM 11th) metastases with considerably good prognosis. The predictive probability of the novel AJCC-CT-pTNM 8th [unification of ypStage II and IIIA, conversion of supraclavicular L/Ns metastases from ypM to ypN] (AIC = 1054.24) was superior to that of the existing AJCC-ypTNM 8th (AIC = 1070.74). The feasibility of novel system was validated using test data from 70 patients. Conclusions: Unification of the AJCC and Japanese systems yields a simpler and more precise predictive system after neoadjuvant chemotherapy.